Limitations of Foundation Business Activities from the Perspective of Law Number 28 of 2004 Concerning Foundations - Mukri, Syarifah Gustiawati; Aji, Ahmad Mukri; Yunus, Nur Rohim (SALAM: Jurnal Sosial dan Budaya Syar-i, 2025)
A foundation as a non-profit legal entity has a vital role in organising social, religious, and humanitarian activities. However, in practice, many foundations are involved in business activities directly and commercially, thus giving rise to legal issues related to violations of the non-profit principle, which is the basis for establishing the foundation. This study aims to analyse the limitations of business activities permitted for foundations according to Law No. 28 of 2004 concerning Amendments to Law No. 16 of 2001 concerning Foundations, and to explain the legal implications for foundations that exceed these provisions. This study uses a qualitative approach with a normative legal research type. The methods used include a statute and conceptual approach, with data sources from laws and regulations, scientific literature, legal documents, and related jurisprudence. The study results indicate that business activities can only be carried out by foundations through capital participation in business entities that are under the intent and purpose of the foundation. Foundations are prohibited from running a business directly and distributing profits to patrons, administrators, and supervisors. Violating these provisions can have legal implications in the form of administrative sanctions up to the foundation's dissolution. Therefore, compliance with legal restrictions is crucial in maintaining the legitimacy and sustainability of the foundation's social function.Keywords: Foundation; Business Activities; Limitations